Determination of Carbamate and Organophosphorus Pesticides in Vegetable Samples and the Efficiency of Gamma-Radiation in Their Removal - Chowdhury, Muhammed Alamgir Zaman; Jahan, Iffat; Karim, Nurul; Alam, Mohammad Khorshed; Abdur Rahman, Mohammad; Moniruzzaman, Mohammed; Siew, Hua Gan; Muhammad Fakhruddin, Abu Naieum (Hindawi Publishing Corporation, 2014)
In the present study, the residual pesticide levels were determined in eggplants (Solanummelongena) (